(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a major cause of chronic kidney disease (CKD) and cardiovascular morbidity worldwide. Despite adequate glycemic control, many patients continue to experience progressive renal dysfunction and adverse cardiovascular outcomes. Dapagliflozin, a sodium-glucose cotransporter-2 (SGLT2) inhibitor, has demonstrated significant cardiorenal protective effects beyond glucose lowering. Aim: To evaluate the cardiovascular and renal outcomes of dapagliflozin in patients with Type 2 diabetes mellitus and chronic kidney disease. Methodology: This prospective observational comparative study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from November 2024 to December 2025. A total of 60 patients with T2DM and CKD were enrolled and divided into two groups. Group A received dapagliflozin 10 mg once daily along with standard therapy, while Group B received standard therapy alone. Renal and cardiovascular parameters including glycated hemoglobin (HbA1c), fasting blood sugar (FBS), body weight, estimated glomerular filtration rate (eGFR), urinary albumin-to-creatinine ratio (UACR), and blood pressure were assessed at baseline, 3 months, 6 months, and 12 months. Statistical analysis was performed using SPSS version 25.0, and a p-value <0.05 was considered statistically significant. Results: Patients receiving dapagliflozin demonstrated significant improvement in glycemic control, renal parameters, and cardiovascular risk factors compared to the control group. HbA1c levels significantly decreased in Group A at 12 months (7.6±0.25 vs 7.91±0.21; p=0.0001). Significant reductions in fasting blood sugar and body weight were also observed. Renal outcomes showed stabilization of eGFR and significant reduction in UACR in the dapagliflozin group, whereas worsening albuminuria was observed in the control group. Improvement in systolic blood pressure was also noted among patients receiving dapagliflozin. Adverse drug reactions such as urinary tract infection and genital infections were more common in the dapagliflozin group, but most were mild and manageable. Conclusion: Dapagliflozin significantly improved glycemic control and provided substantial renal and cardiovascular benefits in patients with Type 2 diabetes mellitus and chronic kidney disease. The drug was generally well tolerated, with mild adverse effects. These findings support the use of dapagliflozin as an effective therapeutic option for improving cardiorenal outcomes in patients with T2DM and CKD.